OCA Oracle Database 11g Database Administration I : a Real-World Certification Guide. - Ries, Steve (Packt Pub., 2013)
Developed as a practical book, ""Oracle Database 11g Administration I Certification Guide"" will show you all you need to know to effectively excel at being an Oracle DBA, for both examinations and the real world. This book is for anyone who needs the essential skills to become an Oracle DBA, pass the Oracle Database Administration I exam, and use those skills in the real world to manage secure, high performance, and highly available Oracle databases.